Einsamkeittrends in der zweiten Lebenshälfte: Befunde aus dem Deutschen Alterssurvey (DEAS). Loneliness trends in the second half of life: Results from the German Ageing Survey (DEAS) - Tesch-Römer, Clemens; Wiest, Maja; Wurm, Susanne; Huxhold, Oliver (Zeitschrift für Gerontologie und Geriatrie, 2013)
Background and research questions: In the current paper, it is analyzed whether the extent of loneliness of adults in the second half of their lives has changed between 1996 and 2008 in Germany. Because patterns of objective social integration have evolved differently in different birth cohorts (familial integration in earlier birth cohorts more fragile, more solid in later birth cohorts), we expected different trends in the extent of loneliness in different birth cohorts. Design and methods: The three waves of the German Ageing Survey (DEAS) constitute the database for the analysis: 1996 (n = 3,979), 2002 (n = 2,766) and 2008 (n = 4,392). Loneliness was measured with the de Jong Gierveld Loneliness Scale. The German Ageing Survey (DEAS) is a nationwide representative survey of the German population aged 40-85 years. Results: Only a minority of people report being very lonely in the second part of life. Between 1996 and 2008, there is a positive trend in the extent of loneliness in the second half of life, i. e., the prevalence of loneliness decreased during this period of time. From 1996 to 2008, the youngest respondents (40-54 years of age) and the middle aged respondents (55-69 years) demonstrated a decline from 1996 to 2002 followed by an increase in loneliness between 2002 and 2008. The oldest respondents (70-85 years of age) experienced a steady decline in loneliness. Gender differences (men are somewhat lonelier than women) remain stable between 1996 and 2008. Discussion and conclusion: While people who are currently old are socially well integrated and, hence, experience loneliness only to a small degree, there is a higher risk for persons who are currently in middle adulthood because their social networks have become increasingly more fragile. Further changes have to be observed. © 2012 Springer-Verlag.
Keywords: Adults; German Ageing Survey (DEAS); Loneliness; Social change; Social isolation